International Migration of Couples - Martin Junge; Martin Munk; Panu Poutvaara (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2015)
We develop a theoretical model regarding the migration of dual-earner couples and test it in the context of international migration. Our model predicts that the probability that a couple emigrates increases with the income of the primary earner, whereas the income of the secondary earner may affect the decision in either direction. We conduct an em-pirical analysis that uses population-wide administrative data from Denmark. The re-sults are consistent with our model. We find that primary earners in couples are more strongly self-selected with respect to income than single persons. This novel result counters the intuition that family ties weaken self-selection.
Keywords: F22; J12; J16; J24; 330; International migration; Family migration; Education; Gender differences; Dual-earner couples